OCCUPATIONAL NOISE INDUCED HEARING LOSS: IT’S FREQUENCY & RISK FACTORS - Pattafi, Muhammad Javid Iqbal; Mumtaz, Nazia; Saqulain, Ghulam (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the frequency and risk factors of occupational noise induced hearing loss.Study Design: Cross sectional study.Place and Duration of Study: Dispensary Unit of Jaith Bhuta Sugar Mill near Rahim Yar Khan, Southern Punjab.from Aug 2017 to Jan 2018.Methodology: This study was conducted using nonprobability consecutive sampling. n=300 workers of bothgenders aged 18-40 years were assessed. Basic demographic parameters, otoscopic examination and Pure Tone Audiometry were used for data collection. The Data was analyzed by using SPSS version 21.Results: Study included 215 (71.7%) males and 85 (28.3%) females with male to female ratio of 2.53: 1 and meanage of 28.34 ± 4.61 years. The frequency rate of hearing impairment (HI) was 90 (30%) out of 300 respondents inthis study. Out of 70 (100%) of respondents were affected with duration of job of 6-10 years. There was significant association between gender, age, education, duration of noise exposure with occupational noise induced hearing loss with p-value